2019
DOI: 10.26508/lsa.201800152
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular matrix protein promotes anillin-dependent processes in theCaenorhabditis elegansgermline

Abstract: Cell division requires constriction of an actomyosin ring to segregate the genetic material equally into two daughter cells. The spatial and temporal regulation of the contractile ring at the division plane primarily depends on intracellular signals mediated by the centralspindlin complex and astral microtubules. Although much investigative work has elucidated intracellular factors and mechanisms controlling this process, the extracellular regulation of cytokinesis remains unclear. Thus far, the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Of these TFs, only NHR-114 had previously been associated with germ cell multinucleation in C. elegans (Gracida and Eckmann, 2013). We used confocal microscopy to analyze the PZ of one-day adults following GTF silencing and detected no MNCs, suggesting that MNC formation is not due to aberrant mitotic division, as shown previously (data not shown) (Lan et al, 2019).…”
Section: Transcriptional Control Of Meiotic Cell Behavior and Gamete ...supporting
confidence: 71%
See 1 more Smart Citation
“…Of these TFs, only NHR-114 had previously been associated with germ cell multinucleation in C. elegans (Gracida and Eckmann, 2013). We used confocal microscopy to analyze the PZ of one-day adults following GTF silencing and detected no MNCs, suggesting that MNC formation is not due to aberrant mitotic division, as shown previously (data not shown) (Lan et al, 2019).…”
Section: Transcriptional Control Of Meiotic Cell Behavior and Gamete ...supporting
confidence: 71%
“…Persistent MNCs would generate multinuclear oocytes and infertile embryos and are therefore cleared by apoptosis prior to generating gametes. Earlier studies showed that failed germ cell division in the PZ and an unstable rachis can cause multinucleation, while in other cases, including in wild-type animals, MNCs form at specific germline structures called folds (Lan et al, 2019;Raiders et al, 2018). In our primary screen, we identified 26 GTFs that have >25% increase in germ lines with MNCs compared to control animals (Table S5-6).…”
Section: Transcriptional Control Of Meiotic Cell Behavior and Gamete ...mentioning
confidence: 99%
“…HMCN1 (also known as fibulin-6) (39) was first found in Caenorhabditis elegans, was named high incidence of males 4 and is one of the genes responsible for increased X chromosome loss in nematodes (40). Functionally, HMCN1 is associated with a hemidesmosome-type structure and is involved in extracellular adhesion, forming cell-cell and cell-basement membrane adhesions that hold cells together and maintain tissue and organ integrity (41).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike germ cells in the mitotic zone of the gonad in C. elegans (Lan et al, 2019), primary spermatocytes are oriented regularly at the proximal end of the gonad in late-L4 worms, and their division entry is stereotyped (Fig. 6).…”
Section: Ordered Cell Division Entry In Primary Spermatocytesmentioning
confidence: 99%